Academic Andragogic Society - continuity and change - Hanna Solarczyk-Szwec (Wydawnictwo Naukowe Uniwersytetu Mikołaja Kopernika, 2018)
In the article the current working conditions of Academic Andragogic Society have been analysed. The challenges of the association were pointed out and there was an attempt to indicate the present role of the Academic Andragogy Association in the world of permanent change. A balance between continuity and change was considered to be the foundation of the organisation's activity.